The Influence Of Emotional Intelligence Towards Academic Achievement Among Gifted Students In Saudi Arabi - Faisal, Al-Sahafi (2016)
This research examined the influence of emotional intelligence (EI) on the academic achievement of gifted students in Saudi Arabia. In particular, it investigated the influence of self-awareness, self-regulation, motivation, empathy, and social skills on the academic achievement of gifted students. The discussion in this study was based on the theoretical framework of Goleman‘s (1995), emotional intelligence theory, Mayer and Salovey‘s model (1995), achievement motivation theory and gender schema theory. These theories were deemed to be appropriate for the current study because they allow the readers to understand how academic achievement could be significantly influenced by EI. One hundred fifty respondents consisting of both male and female gifted students were involved in the quantitative study. Meanwhile, 10 teachers and 30 gifted students were invited to participate in the qualitative study. Questionnaires and interview protocol were the instruments used to gather data for the quantitative and qualitative studies, respectively. Multiple regressions was used to analyze and interpret the quantitative data, particularly the influence of EI (self-awareness, self-regulation, motivation, empathy, and social skills) on the academic achievement of gifted students. This technique was also applied with the effect size to determine the EI elements that could best predict the academic achievement of students. T-test was adopted to identify the significant difference of EI among the students based on gender.